PENGATURAN PERLINDUNGAN BATIK YOGYAKARTA SEBAGAI EKSPRESI BUDAYA TRADISIONAL: Protection of Yogyakarta Batik as a Expressions of Folklore - Viola, Salsabilla Ade; Bustani, Simona (Faculty of Law, Universitas Trisakti, 2025)
Batik is the art of writing or painting on cloth. Yogyakarta batik has now become one of Indonesia’s national batik symbols and identities. If traced, the early existence of Yogyakarta Batik is closely related to the batik tradition that gew and developed during the mataram kingdom. The problem’s formulation raised is how the regulation of the protection of expression of folklore of Yogyakarta Batik. The writing of this journal uses a normative research type that is normative analytical in nature using the law approach and prioritizing secondary data. Considering the research’s finding, it can be concluded that the regulation of the protection of Yogyakarta Batik as a Expression of folklore is based on Law No. 28 of 2014 concerning Copyright, the Law on the Promotion of Culture, and Regional Regulation Number 13 of 2019 in relation to the Development and Maintenance of Batik Jogja. However, based on these regulations, there is no regulation related to maximum protection if there is Batik Jogja claimed or recognized by foreign parties so that a firmer and more comprehensive policy is needed as well as close cooperation between the central and regional governments.